Role of flm Locus in Mesophilic Aeromonas Species Adherence - Gryllos, Ioannis (American Society for Microbiology, 2001)
The adherence mechanism of Aeromonas caviae Sch3N to HEp-2 cells was initially investigated through four mini-Tn5 mutants that showed a 10-fold decrease in adherence. These mutants lost motility, flagella, and their lipopolysaccharide (LPS) O antigen (O-Ag). Three genes, flmB-neuA-flmD, were found to be interrupted by the transposon insertions; additionally, two other genes, one lying upstream (flmA) and one downstream (neuB), were found to be clustered in the same operon. While the flmA and flmB genes were present in all mesophilic Aeromonas spp. (A. hydrophila, A. caviae, A. veronii bv. veronii, and A. veronii bv. sobria) tested, this was not the case for the neuA-flmD-neuB genes. Construction and characterization of flmB insertion mutants in five other mesophilic Aeromonas strains revealed the loss of motility, flagella, and adherence but did not alter the LPS composition of these strains. Taking the above findings into consideration, we conclude (i) that flagella and possibly the LPS O-Ag are involved in the adherence of the mesophilic Aeromonas to human epithelial cells; (ii) flmA and flmB are genes widely distributed in the mesophilic Aeromonas and are involved in flagella assembly, and thus adherence; and (iii) in A. caviae Sch3N the flmA and flmB genes are found in a putative operon together with neuA, flmD, and neuB and are involved in LPS O-Ag biosynthesis and probably have a role in flagellum assembly.